Mecanismos comportamentais e moleculares envolvidos na interação entre as substâncias de abuso e os fatores de risco para o desenvolvimento da dependência - Leão, Rodrigo Molini (Universidade Federal de São Carlos, 2013)
Tobacco and ethanol are the most used drugs in the world and often co-abused. An important issue in the field of drug abuse research is the characterization of risk factors related to increased vulnerability to drug addiction. In the present study we investigated in rats: a) the effects of exposure to variable stress on nicotine-induced locomotor activation, CREB and ERK activities in the prefrontal cortex, nucleus accumbens and amygdala and nicotine intravenous self-administration; b) whether previous exposure to cocaine could affect nicotine seeking behaviors, and if this phenomenon could be related to alterations in the BDNF, TrkB, DYN, Mi-Opio, NPY and CRFR1 gene expression in the nucleus accumbens; c) whether repeated nicotine treatment could induce anxiety-like behavior, which in turn increases alcohol intake; d) the effect of simultaneous nicotine treatment during the transition to development of alcohol dependence and whether that is mediated by activation of neuronal ensembles in different parts of the brain. We found: the variable stress exposure caused cross sensitization with nicotine, increased the nicotine selfadministration behavior and decreased CREB activity in mesencephalic areas; the pretreatment with cocaine caused sensitization of cocaine motor response, locomotor cross-sensitization with nicotine, and increased motivation to nicotine intake; the pretreatment with nicotine increased the anxiety-like behavior and the motivation to ethanol intake; the simultaneous administration of nicotine and ethanol vapor exposure speed up the escalation of ethanol self-administration, increased the motivation and the compulsivity to ethanol intake and these behaviors could be related to activation of extended amygdala and mesocorticolimbic systems. Our results suggest that additional factors to the drug use such as stress and preexposure to other drug could increase the vulnerability to addiction.
Keywords: Psicofarmacologia; Dependência; Nicotina; Etanol; Estresse; Alterações moleculares; Dependência à substâncias de abuso; Comportamento animal; Drug addiction; Nicotine; Ethanol; Stress; Animal behavior; Molecular alterations; CIENCIAS BIOLOGICAS::FISIOLOGIA